PS02.121: INTENSIFIED IMRTWITH CARBOPLATIN AND PACLITAXEL IN LOCALLY ADVANCED ESOPHAGEAL CANCER: AN ANALYSIS ON EARLY OUTCOME. (14th September 2018) - Innocente, Roberto; Navarria, Federico; Palazzari, Elisa; Matrone, Fabio; Farina, Eleonora; Fanetti, Giuseppe; Boz, Giovanni; Gigante, Marco; Foltran, Luisa; Castoro, Carlo; Ubiali, Paolo; Petri, Roberto; et al.
Abstract: Background: Evaluate safety, feasibility and efficacy of an intesified IMRT and concomitant carboplatin and paclitaxel-based chemotherapy (Carbo/Tax CT) in patients (pts) with locally advanced esophageal cancer (LAEC) treated at our Institution Methods: We retrospectively analyzed acute toxicity (according to CTCAE 4.0 scale), compliance and response to treatment in a series of consecutive patients treated, between February 2016 and February 2018, with intensified radiotherapy (IMRT) and weekly concurrent carboplatin and paclitaxel-based chemotherapy (CT) according to the CROSS trial. Results: Thirty-four consecutive pts, 30(88%) males and 4 (12%) females, were treated. The median age was 68.5 yrs (range 46–83) and the ECOG Performance status ranged from 0 to 2. The diagnosis was adenocarcinoma in 15 pts (44%), squamous-cell carcinoma in 18 pts (53%) and undifferentiated carcinoma in 1 pt (3%). Two pts (6%) had a T2, 26 pts (76.4%) a T3 and 6 pts (17.6%) a T4 disease, respectively; 5 pts (15%) were N0, 21 pts (62%) N1 and 8 pts (23%) N2, respectively. Tumor involved the cervical esophagus in 3 pts (9%), the thoracic esophagus in 24 pts (70.5%) and the gastroesophageal junction in 7(20.5%). All pts underwent concurrent chemoradiotherapy (CRT), with IMRT technique, consisting of 45 Gy/25 frs to PTV1 (the primary gross tumor volume and the regional nodes), a simultaneous integrated boost ranging from 52.5Gy to 54Gy to PTV2 (gross tumor volume) and weekly concurrent carboplatin (AUC2) and paclitaxel (50mg/m 2 ). Induction CT was administered to 6 pts. All pts completed the RT schedule. The median number of CT cycles was 3 (range 1–5) and 11 pts (32%) received 4 to 5 cycles of CT. Two adverse reactions to paclitaxel were reported. There were no major non-hematological adverse effects, the most common were nausea and vomiting (10%), and dysphagia (7%). Leukopenia was reported in 20 pts (71%), G3 in 2 pts (10%) and G2 in 18 (90%), respectively. G2 anemia occurred in 2 pts while G2 thrombocytopenia was reported in 3 pts (10%). Among the 30 evaluable pts (restaging is ongoing in 4 pts) a clinical complete response (PET, endoscopy and biopsy) was observed in 11 pts (37%), 7 with adenocarcinom and 4 with squamous cell carcinoma. Partial response was observed in 11 pts (37%) and 8 (26%) showed progressive disease. Total esophagectomy with radical lymphadenectomy, performed in 11 pts, showed a pathologic complete response in 6 pts (54%). Conclusion: Intensified IMRT with concomitant Carbo/Tax CT in pts with LAEC seems to be safe and effective. These promising results need to be confirmed in all pts evaluated in this multimodality program Disclosure: All authors have declared no conflicts of interest.